2017
DOI: 10.4103/ijri.ijri_373_16
|View full text |Cite
|
Sign up to set email alerts
|

MR fistulography with percutaneous instillation of aqueous jelly: A cost effective technique innovation

Abstract: Background:Perianal fistula is a commonly encountered condition in routine surgical practice. Accurate presurgical mapping of these tracts is vital to prevent recurrence. We have assessed the effectiveness of percutaneous instillation of aqueous jelly prior to magnetic resonance (MR) fistulography.Aims and Objectives:To study the role of percutaneous instillation of aqueous jelly in fistulous tracts prior to MR fistulography.Materials and Methods:All patients with active discharge, referred for MR fistulograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Aggarwal et al performed percutaneous instillation of aqueous jelly into the perianal fistulas in 64 subjects and the postjelly MR fistulography findings were compared with the surgical results, which showed a sensitivity of 97% and positive predictive value of 100% in comparison with peroperative findings. 13 Waniczek et al performed an MRI after injecting a few drops of gadolinium mixed with saline through the external fistulous opening in 14 subjects, and the surgical findings were consistent with radiological descriptions of 13 MRI fistulographies. 9 Likewise, in our study, it was possible to diagnose the type of tract and compare it with the plain MRI findings in all 29 patients postjelly injection,.…”
Section: Discussionmentioning
confidence: 76%
“…Aggarwal et al performed percutaneous instillation of aqueous jelly into the perianal fistulas in 64 subjects and the postjelly MR fistulography findings were compared with the surgical results, which showed a sensitivity of 97% and positive predictive value of 100% in comparison with peroperative findings. 13 Waniczek et al performed an MRI after injecting a few drops of gadolinium mixed with saline through the external fistulous opening in 14 subjects, and the surgical findings were consistent with radiological descriptions of 13 MRI fistulographies. 9 Likewise, in our study, it was possible to diagnose the type of tract and compare it with the plain MRI findings in all 29 patients postjelly injection,.…”
Section: Discussionmentioning
confidence: 76%
“…Contrast enhanced FS T1 imaging sequence can better identify the primary fistulous tract, internal openings, lateral ramifications, as well as improves visualization of the smaller tracts. [1] Gadolinium shortens the T1 time and hence makes the walls of the fistulae more evident (Figure 6). With gadolinium, the chronic tracts & scar tissue may not show any enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous jelly has a long T2 relaxation time; giving it an intrinsic contrast (Figure 8) on T2 weighted imaging. [1] Since, it is an easy procedure; it can be done on a regular basis for better outcome. Our study demonstrated similar findings with both the methods of contrast administration that were studied with the percutaneous instillation of gadolinium (Figure 9) showing marginally better results with the identification of secondary tracts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations